2022
DOI: 10.1111/cod.14209
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of skin diseases in healthcare workers before and during the COVID‐19 pandemic at Trieste hospitals (northeastern Italy)

Abstract: Background Occupational skin diseases (OSDs) are common in healthcare workers (HCWs). Objectives To investigate and compare the incidence and clinical features of OSDs among HCWs before and during the COVID‐19 pandemic. Materials and Methods Incident cases of OSDs were investigated in the cohort of HCWs at Trieste Hospitals from 1 July 2018 (3340 workers) to 31 October 2021 (137 532 person‐months). Results The mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…When the COVID-19 pandemic started, all HCWs and apprentices had to use alcohol-based sanitizers to reduce their use of soaps. The effectiveness of the adopted preventive measures has also been evaluated in HCWs in our hospitals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the COVID-19 pandemic started, all HCWs and apprentices had to use alcohol-based sanitizers to reduce their use of soaps. The effectiveness of the adopted preventive measures has also been evaluated in HCWs in our hospitals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Unfortunately, those measures could also lead to skin damage and the development of a new inflammatory skin disease or the exacerbation of an existing one, with health professionals especially under the risk of developing those changes. [2][3][4][5][6] In Croatia, antiseptics and disinfectants had, according to financial indicators, the largest consumption of all dermatologicals (Anatomical Therapeutic Chemical (ATC) Classification group D), accounting for 23% of total consumption. A report on drug utilisation by the Agency for Medicinal Products and Medical Devices of Croatia recognised chlorhexidine as the most used drug in the entirety of ATC group D. 7 Testing the skin's response to irritants and the effectiveness of different treatment options could possibly be performed on patients with active irritant contact dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Sanitisers with more than 60% ethanol or 70% isopropyl alcohol content are recommended, with some sanitisers also containing various additional antiseptics, such as chlorhexidine, povidone iodine or quaternary ammonium compounds 1 . Unfortunately, those measures could also lead to skin damage and the development of a new inflammatory skin disease or the exacerbation of an existing one, with health professionals especially under the risk of developing those changes 2–6 . In Croatia, antiseptics and disinfectants had, according to financial indicators, the largest consumption of all dermatologicals (Anatomical Therapeutic Chemical (ATC) Classification group D), accounting for 23% of total consumption.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several questionnaire studies among HCWs during the COVID-19 pandemic have shown a high frequency of self-reported facial adverse skin reactions related to the use of face masks. [2][3][4] Commonly reported adverse skin reactions include eczema, acneiform and rosacea-like lesions, erythema and ulcers [5][6][7][8][9][10] Transient erythema can be difficult to differentiate from urticaria which can be induced by pressure, friction and a wide range of chemical substances. 11 In one report, contact urticaria was suspected clinically in 3 out of 13 HCWs with facial adverse skin reactions to respirators.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly reported adverse skin reactions include eczema, acneiform and rosacea‐like lesions, erythema and ulcers 5–10 Transient erythema can be difficult to differentiate from urticaria which can be induced by pressure, friction and a wide range of chemical substances 11 . In one report, contact urticaria was suspected clinically in 3 out of 13 HCWs with facial adverse skin reactions to respirators 12 .…”
Section: Introductionmentioning
confidence: 99%